Model Keputusan Pembelanjaan Usaha Kecil Mikro dan Menengah (UMKM) Wisata Kuliner Di Pulosari Malang - Dewi Nurjannah; Sudarmiatin Sudarmiatin; Agus Hermawan (Jurnal Syntax Transformation, 2021)
Small and medium-sized micro enterprises (MSMEs) are the most numerous business groups. The existence of MSMEs has an important role in improving people's living standards, and in economic development in Indonesia. These conditions must be utilized properly by the government, the community and financial institutions to better participate in developing MSMEs in Indonesia for example, the government and financial institutions support and help overcome capital problems. This research aims to find out the decisions / spending / sources of funds used in small businesses micro culinary tourism in Pulosari Malang, this study also describes the barriers of access to sources of funds in micro and small culinary tourism businesses in Pulosari Malang, so that a Model can be made for Spending Decisions for small businesses micro culinary tourism in Pulosari Malang. To achieve this goal, research is designed with a focus on identifying various sources of funds and barriers to access to sources of funds in small businesses micro culinary tourism in Pulosari Malang, so that it can be determined the model of development of Spending Decisions on small businesses micro culinary tourism in Pulosari Malang which is then evaluated and followed up to increase capital and business improvement. This type of qualitative research, with data collection techniques conducted with observations, interviews, and questionnaires. The data analysis used is the analysis of the inscription. The results of the study proved that MSMEs using their own capital, foreign capital and mixed capital with barriers to limited access to capital due to administrative requirements, human resource limitations in the field of financial reporting and spending decision models on MSMEs that use their own capital and foreign capital should use the right composition, above the ratio of 3: 1 to be stronger in capital for business development